A reorganização da vida e da sexualidade de pessoas que vivem com HIV/AIDS acompanhadas em um hospital-dia - Juliano, Fernanda Maria Souza (2022)
With the development of combined antiretroviral therapy (ART), there was an increase in quality of life, but the stigma surrounding the disease persists today. The impact of the diagnosis interferes with sexuality, self-image, relationships, and echoes as a whole in the individual's life. In view of this, the present research aimed to understand how the reorganization of the life and sexuality of patients being followed up at the Esterina Corsini Day Hospital takes place, in the period of at least one year after diagnosis. For this, interviews were carried out with generating questions preceded by the characterization of the subjects. The Collective Subject Discourse (CSD) technique by Lefèvre and Lefèvre (2005) was chosen to organize the data. The results led to three thematic axes that encompassed discussions about ways of coping with the disease in the areas: subjective, social and sexuality, each with three CSD. The results of this research covered: re-signification from the disease, biopsychological repercussions of the diagnosis and silence with self-protection; fear of rejection, experience of prejudice and segregation and association of HIV with death; adaptations in the field of sexuality, dispensability of sex with the search for new ways to live life and fear, deprivation and decreased libido. These aspects are discussed from a psychoanalytic perspective, allowing for an understanding of the ways of coping with HIV-positive subjects with regard to life and sexuality. It is concluded that there is no single way to reorganize the field of sexuality, considering that each subject has different intrinsic and extrinsic resources, which may or may not lead to acceptance of the disease and management of difficulties in living with HIV/AIDS. However, it is correct to say that the stigmas rooted in the disease affect and influence all subjects, who have to deal first with the deconstruction of self-prejudice in order to start with ways of coping. Health Descriptors: HIV infections, Sexuality, social stigma, patient care.